Peningkatan Stabilitas Penggunaan Berulangd an Stabilitas Termal Enzim Lipase melalui Imobilisasi pada Zeolit Alam - Fandhi Adi Wardoyo; Aprilia Indra Kartika (Jurnal Labora Medika, 2018)
Thermal stability and lifetime stability for immobilization lipase on zeolit by absorption technique has been carried out. Immobilization of lipase on zeolit was performed via physical adsorption. This reseacrh aimed to determine the effectiveness of pancreatic lipase immobilization in term of thermal and lifetime stability of the hydrolysis activity. The result of this research proved that pancreatic lipase was able to immobilized to zeolit by using the physical adsorption. Immobilized lipase shows better lifetime stability than the free lipase. Immobilized enzyme catalyzed reaction has a lower decreases free fatty acid than that of the free enzyme. Lower decline of value suggests the enzyme is more stable for repeated use. The immobilized lipase was able to maintain its activity after multiple-uses up to four reaction cycles. Similar trend was also observed for thermal stability study. Immobilized lipase shows a higher thermal stability that that shown by free lipase. Immobilized lipase on zeolit was also able to maintain its activity at 40oC.